A retrospective investigation to establish new screening approach for the detection of patients at high risk of Fabry disease in male left ventricular hypertrophy patients. Issue 4 (October 2022) - Kubo, Toru; Amano, Masashi; Takashio, Seiji; Okumura, Takahiro; Yamamoto, Saori; Nabeta, Takeru; Oikawa, Masayoshi; Kurisu, Satoshi; Ochi, Yuri; Sugiura, Kenta; Baba, Yuichi; Kuroiwa, Hajime; et al.
Abstract: Background: The prevalence of Fabry disease (FD) in male patients with left ventricular hypertrophy (LVH) is about 1%. From the perspective of performing more efficient screening with measurement of α-galactosidase (α-Gal) activity, it is important to raise the pretest probability. Methods: We retrospectively investigated the prevalence of FD in 701 male patients with LVH who already had been screened by measurement of α-Gal activity in eight hospitals. From the viewpoint of enzymatic screening, we validated previously reported clinical features of FD including the electrocardiographic and echocardiographic characteristics with comparing each clinical determinant between patients with FD and non-FD patients. We finally aimed to establish a new screening approach for the detection of patients at high risk of FD. Results: There were five FD patients (0.7%) in the 701 male patients with LVH. Those five patients with FD all had the cardiac variant type and age at detection of LVH was ≥35 years in all patients. In LVH patients with LV ejection fraction (EF) ≥ 50%, Pend-Q interval < 40 msec, SV1 + RV5 > 4.0 mV, and diffuse LVH were important determinants of FD. In LVH patients with LVEF < 50%, asymmetric septal hypertrophy and posterior wall motion abnormality seemed to be associated with FD. Conclusions: In our retrospective study, the prevalence of FD in male patients with LVH was found to be 0.7%. We established the efficient combinations of clinical determinants using age at detection of LVH, Pend-Q interval, high voltage, and LVH pattern in an echocardiogram. Graphical abstract: Unlabelled Image Highlights: A retrospective study to establish new screening approach for Fabry disease in left ventricular hypertrophy (LVH) Of the 701 male patients with LVH screened by enzyme activity, 0.7% had Fabry disease. All five patients with Fabry disease had the cardiac variant type with late-onset. Pend-Q interval, high voltage, and LVH morphology were important in detecting Fabry disease.